Oral Health Knowledge, Attitude, and Approaches of Pre-Primary and Primary School Teachers in Mumbai, India - Ankita Mota; Kunal C. Oswal; Dipti A. Sajnani; Anand K. Sajnani (Scientifica)
Background. School teachers have an internationally recognized potential role in school-based dental education and considerable importance has therefore been attributed to their dental knowledge. The objectives of this study were to determine the oral health related knowledge, attitudes, and approaches of pre-primary and primary school teachers in the city of Mumbai. Methods. The descriptive cross-sectional study was conducted in the suburban regions of Mumbai using a self-administered questionnaire and involved 511 teachers. Results. Teachers demonstrated inappropriate or incomplete knowledge regarding children’s oral health. Only 53.2% knew that an individual has two sets of dentition. Moreover, only 45.4% of the teachers knew that a primary dentition consists of 20 teeth. Only 56.9% of the teachers asked their children to clean their mouth after snacking during school hours. 45.0% of the teachers were unaware of fluoridated tooth pastes whilst 78.9% of them were unaware of school water fluoridation programmes. Also, 54.8% of the teachers never discussed the oral health of children with their parents during parents meet. Conclusions. The studied school teachers demonstrated incomplete oral health knowledge, inappropriate oral practices, and unfavourable approaches to children’s oral health. There is a definite and immediate need for organized training of school teachers on basic oral health knowledge.